HV-KIC property charts of cemented carbides: A comprehensive data collection. (February 2022) - Chychko, Andrei; García, José; Collado Ciprés, Verónica; Holmström, Erik; Blomqvist, Andreas
Abstract: In this work more than 2500 published experimental data on hardness and indentation fracture toughness of cemented carbides during the last 40 years have been collected. The significant number of samples displays the influence of microstructure, chemical composition, and processing on the hardness - toughness relationship of cemented carbides. Selected two-dimensional plots are presented and discussed as an example of visualization of the available experimental information. This collected record can serve as an initial reference set for the cemented carbide community using all available shared knowledge organized in one well-structured database. Graphical abstract: Unlabelled Image Highlights: 2500 published experimental data on hardness and indentation fracture toughness of cemented carbides Shared knowledge of cemented carbides during last 40 years organized in structured database Microstructure, chemical composition and processing influence on the Hv-KIC of cemented carbides Selected two-dimensional Hv-KIC plots for visualization of the available experimental information